OBESITY AND CARDIOVASCULAR DISEASE: A SYSTEMATIC REVIEW - Olivia, Andria (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The pathophysiology of obesity includes a function for the equilibrium between the number of calories consumed and the quantity of energy expended, which is then followed by a resetting of body weight. On the other hand, this is not as straightforward as solving an equation, and there are a number of secondary processes that contribute to this difficult condition. It is believed that obesity is a state of inflammation because obese people have a greater amount of fat tissue and a lower level of adiponectin. This means that obese people are less able to stop the processes that generate inflammation, which in turn keeps the inflammation going. This adipocyte dysregulation adds to the imbalance of homeostasis as well as pro- and anti-inflammatory mechanisms in the body, which in turn contributes to metabolic difficulties caused by obesity as well as vascular damage that leads to changes in cardiometabolic function. The structure and function of the cardiovascular system, as well as the hemodynamics of the blood, are all severely influenced by obesity. Obesity also has a negative impact on the metabolic processes of the body. When a person is obese, their total blood volume as well as their cardiac output go up, which also leads to an increase in the amount of work that their heart has to do. Patients who are obese often have a higher cardiac output but a lower level of total peripheral resistance at any given level of arterial pressure. This is because obesity typically causes a decrease in total peripheral resistance. Previous research has demonstrated that patients or individuals with a body mass index (BMI) that is greater than 25, have a high risk connected with the risk of cardiovascular disease (CVD). In addition to this, the strength of this connection grows with advancing age.